Skin Cancer - A World-Wide Perspective - Dummer, Reinhard; Pittelkow, Mark R.; Iwatsuki, Keiji; Green, Adèle; Elwan, Nagwa M. (Springer Berlin Heidelberg : Imprint: Springer, 2011)
The dramatic increase in the incidence of skin cancers is a major concern worldwide and relates not only to melanoma but also to other cancers, including Merkel cell and basal cell carcinomas. Recently, the WHO has summarized the genetic and pathologic features of skin cancers in its book series. However, the WHO's proposed classification of certain disease entities, such as basal cell carcinomas, is still novel for many dermatologists. This book covers the entire spectrum of cutaneous malignancies in accordance with the new WHO classification. Epidemiology, pathogenesis, diagnosis, and therapy are all reviewed in detail, and care is taken to link the diagnostic and genetic features to optimized therapeutic strategies. In order to reflect the worldwide activities in the field, the editors have brought together leading researchers and clinicians from every continent to communicate their individual experiences and expertise. The result is a unique compilation of current medical and molecular knowledge about skin cancers. It is anticipated that this book will remain a basic reference for many years to come.